Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Membeli Sepeda Motor Second Pada Dialer Tugu Muda Motor Muara Bulian - Ahmad Fithoni; Afriantoni Afriantoni (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
This study aims to analyze the effect of Marketing Mix (Product, Price, Place and Promotion) on Consumer Decisions to buy Second Motorcycles at the Muara Bulian Motor Tugu Dialer. This type of research is quantitative descriptive while the method of data collection is done by giving questions to respondents with questionnaire guidance. The sampling technique uses the Accidential Sampling technique. The sample in this study were 45 respondents. The results of the analysis in this study are as follows, The Effect of Product, Price, Place and Promotion on Consumer Decisions in buying a Second Motorcycle at the Tugu Muda Motor Dialer is explained as follows. From the partial test results on the product variable obtained 2,503> 1,68023, the results of the price test variable obtained 2,241> 1,68023, the test results on the location variable obtained 3,296> 1,68023 and the test results on the promotion variable obtained 3,134> 1,68023 all the value of t count is greater than t table which shows that the Independent variable of each mqsing has an influence on the Dependent variable. While the Simultaneous test results, the F value can be counted 47.128 greater than F table 2.56 or (47.128> 2.56) which shows that all Independent variables simultaneously influence the Dependent Variables. From the results of the coefficient of determination (R2) test is 0.767, it shows that the Marketing Mix variable contributes 76.7% to consumer decisions, while the remaining 23.3% is the contribution of other variables not examined in this study.